RATIONALIZING REVELATION IN THE MALAY-INDONESIAN WORLD: THE DECONSTRUCTION OF FATALISM AND TAQLĪD IN OEMAR BAKRY’S TAFSIR RAHMAT - Muhammad Dhiya'ul Umam; Ika Yunia Fauzia; Abdul Kadir Riyadi; Moh. Addib Amrullah (Tanzil: Jurnal Studi Al-Quran, 2026)
The tension between theological fatalism (jabr) and modernist activism defined much of 20th-century Indonesian Islamic thought, shaping the socio-political trajectory of the post-colonial nation. Within this intellectual contestation, vernacular exegesis emerged as a crucial medium for reform, translating elite theological debates into mass pedagogy. While previous studies have predominantly highlighted the pedagogical and scientific features of Oemar Bakry’s Tafsir Rahmat (1983), the specific theological mechanisms he employs to dismantle deterministic logic remain underexplored. This article investigates how Bakry’s exegesis operationalizes a Theology of Progress to explicitly deconstruct traditionalist passivity and the epistemological stagnation caused by blind imitation (taqlīd). Employing a qualitative history of ideas approach within an adabī ijtimā‘ī (socio-literary) framework, the study utilizes a thematic data coding system to analyze Bakry’s interpretation of key verses regarding socio-historical agency, calamity, and cosmology. The findings reveal a tripartite strategy of rationalization. First, Bakry reinterprets Q.S. Ar-Ra‘d [13]: 11 to frame historical change as a mechanical consequence of human effort governed by sunnatullāh (God’s natural laws), unequivocally rejecting deterministic readings that paralyze social mobility. Second, he utilizes the Minangkabau reformist maxim reason before surrender (habis akal baru tawakal) to interpret Q.S. Ash-Shūrā [42]: 30, redefining natural disasters as verifiable consequences of human negligence and ecological mismanagement rather than inexplicable divine trials. Third, the exegesis purges unverifiable folklore (isrā’īliyyāt) while simultaneously integrating modern scientific terminology, notably translating al-samāwāt as space (ruang angkasa) to bridge scriptural revelation with the Space Age. The study concludes that Tafsir Rahmat serves as a critical instrument of deliberate social engineering. By translating the intellectual elitism of global Islamic modernism into an accessible vernacular pedagogy, Bakry successfully deconstructs the fatalistic mindset to reconstruct the Indonesian Muslim subject from a passive recipient of fate into an active, rational agent of post-colonial history and nation-building.